Analisis Novo Learning: Media Pembelajaran Bahasa Inggris dalam Meningkatkan English Skills Mahasiswa UPI Kampus Serang - Nurul Safira (FONDATIA, 2023)
This study aims to determine the influence of Novo Learning in improving student English skills. The type of research used is a quantitative approach. As for the research population, it is the 2nd semester students of UPI Serang Campus who took English courses with a sample of 30 people. The questionnaire data collection technique uses the likert scale method. In addition, the data analysis techniques carried out by researchers are descriptive statistics and inferential statistics. The results showed that there is an influence of Novo Learning: English digital learning media in improving student English skills. This was proved through a simple linear regression test Y = 3.117 + 0.868 X with a correlation value of 0.842 and a regression coefficient validity test using a t test with a calculated ratio of 5.757 > a ttabel of 2.0452. In addition, Novo Learning has a contribution of 70.9% to the English skills variable and another 29.1% is influenced by other factors outside the Novo Learning variable.